2010
DOI: 10.15288/jsad.2010.71.761
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-Specific Alcohol Expectancies in Couples With Concordant and Discrepant Drinking Patterns

Abstract: ABSTRACT. Objective: Despite growing evidence that the marital problems typically attributed to heavy drinking are stronger for couples in which only one partner is a heavy drinker than in couples in which both partners are heavy drinkers, relatively little research has examined factors that may serve to maintain particular drinking confi gurations. The current research examines the association between the confi guration of partners' drinking and relationship-specifi c alcohol expectancies. Method: Data are fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…These data are similar to a study conducted in Alberta, Canada 37 and in Russia 38 . In general, a stable relationship has been associated with better health conditions 39 and a decrease in alcohol use disorders is also observed in older relationships 40 . According to Leonard 41 transition to a stable relationship can cause a decrease in alcohol use in the same way that divorce can trigger abusive use of this substance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are similar to a study conducted in Alberta, Canada 37 and in Russia 38 . In general, a stable relationship has been associated with better health conditions 39 and a decrease in alcohol use disorders is also observed in older relationships 40 . According to Leonard 41 transition to a stable relationship can cause a decrease in alcohol use in the same way that divorce can trigger abusive use of this substance.…”
Section: Discussionmentioning
confidence: 99%
“…According to Leonard 41 transition to a stable relationship can cause a decrease in alcohol use in the same way that divorce can trigger abusive use of this substance. Among men, alcohol consumption is also observed to be lower for individuals in stable relationships, so, marital status could be a protective factor [39][40] . In consistency with the literature, this study found an association between alcohol use disorders and use of tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study of married couples, Leonard and Mudar (2004) found that husbands' infl uence on wives' drinking over the fi rst year of marriage was greater among wives who had stronger positive expectancies (i.e., a composite of intimacy/openness, social pleasure/fun, and sexual-enhancement expectancies). In addition, in a cross-sectional examination of married couples, Derrick et al (2010) showed that wives in couples in which both members drank heavily reported stronger intimacy expectancies compared with heavy drinking husbands and couples of other drinking types. Finally, in a study of women only, Kelly et al (2002) found that women who were problem drinkers and/or in a distressed relationship reported greater expectancies for increased intimacy and relationship effi cacy effects compared with women who were not problem drinkers or in distressed relationships.…”
Section: Relationship-specifi C Alcohol Expectanciesmentioning
confidence: 99%
“…Research indicates that certain relationship drinking contexts, particularly drinking with one's partner (vs. drinking apart), appear to be adaptive mechanisms for relationship functioning in that they are associated with greater intimacy and relationship satisfaction and fewer relationship problems (Homish and Leonard, 2005;Levitt and Cooper, 2010). A growing literature shows that couple members hold relationshipspecifi c alcohol expectancies (RSAE) that refl ect beliefs about the likelihood of alcohol's effects on distinct relationship domains (e.g., increased intimacy) that are associated with relationship drinking behaviors (Derrick et al, 2010;Leonard and Mudar, 2004;Levitt and Leonard, 2013). This research supports motivational theories of alcohol use (e.g., Cooper et al, in press;Cox and Klinger, 1988) including a relationship motivation model (Leonard and Mudar, 2004), which posits that alcohol use in romantic relationships is motivated by relationship-specifi c factors and is associated with relationship-specifi c consequences.…”
mentioning
confidence: 99%
“…More positive alcohol expectancies, or an individual’s beliefs about the effects of alcohol, predict heavier alcohol consumption (see Jones, Corbin, & Fromme, 2001 for a review; Leonard & Homish, 2008). Relationship-specific alcohol expectancies address one’s beliefs about the effects of drinking on their romantic relationship (e.g., Derrick, Leonard, Quigley, Houston, Testa, & Kubiak, 2010; Leonard & Mudar, 2004; Levitt, Derrick, & Testa, 2014; Levitt & Leonard, 2013). These types of expectancies include believing that drinking will lead to greater intimacy/openness, social pleasure/fun, sexual enhancement, or power/assertion in their relationship.…”
Section: Relationship-specific Alcohol Expectanciesmentioning
confidence: 99%